Macrofauna associated with a recently described bryozoan species in the Eastern Harbour of Alexandria, Egypt - ELSAYED, RASHA HAMDY; DORGHAM, MOHAMED MOUSSA (Mediterranean Marine Science, 2019)
The bryozoan Calyptotheca alexandriensis was recorded for the first time two years ago as a new species from the Eastern Harbour of Alexandria, Egypt. Knowledge about the ecology of this bryozoan and the associated fauna is completely lacking. The present study is the attempt to identify the fauna associated with this bryozoan species, through approximately bimonthly sampling from October 2017 to August 2018. A total of 43 animal species were associated with the colonies of C. alexandriensis, belonging to nine taxonomic groups, including polychaetes (21 species), crustaceans (13 species), molluscs (3 species), ascidians, bryozoans, cnidarians, echinoderms, sipunculids, and sponges (one species each). Juvenile shrimps, fish larvae and eggs of different animals were also found. The numerical abundance of the associated fauna fluctuated between 1279.3 individuals/kg in winter to 3041 individuals/kg in autumn. Crustaceans were the most abundant group, constituting 90.5% of the total associated fauna, mainly due to the amphipod Elasmopus pectenicrus (75.4%), beside other crustaceans like Jassa marmorata (6.2) and Apohyale perieri (3.7%). In contrast, polychaetes were markedly less abundant, forming 7.9% of the associated fauna, with the dominance of Pseudonereis anomala (3.5%). Spring and summer communities were more diverse (30-32 species) than the autumn and winter communities (16 and 25 species, respectively). The Shannon diversity index presented low diversity of the associated fauna, varying seasonally between 0.56 in summer and 1.6 in winter, with evenness fluctuating from 0.16 in summer to 0.50 in winter.